Integrating Cognitive Behavioral Therapy with Islamic Principles to Foster Psychological and Spiritual Well-Being - Syed Zainal Ariff, Sharifah Nadirah (Jurnal Psikologi, 2025)
Cognitive Behavioral Therapy (CBT) is an established method for treating mental health conditions such as anxiety and depression. However, its Western epistemology may limit cultural resonance for Muslim clients whose worldviews are shaped by Islamic theology. This paper proposes a faith-sensitive therapeutic model that integrates core Islamic concepts, such as sabr (patience), tawakkul (trust in God), muhasabah (self-reflection), and dhikr (remembrance), into CBT’s cognitive and behavioral tools. This spiritually grounded model promotes emotional healing while nurturing resilience and divine consciousness. It offers clinicians a culturally congruent framework that aligns with Muslim identity, values, and belief systems. The model enhances therapeutic alliance and supports both psychological and spiritual well-being. Its novelty lies in harmonizing traditional CBT with Islamic principles to foster deeper and longer-lasting healing.